Remote control of cascading dynamics on complex multilayer networks. (12th April 2019) - Liu, Run-Ran; Jia, Chun-Xiao; Lai, Ying-Cheng
Abstract: To develop effective control strategies to enhance the robustness of multilayer networks against large-scale failures is of significant value. We articulate the idea of 'remote control' whereby adaptive perturbations to one network layer are able to enhance the resilience of not only itself but also other interconnected network layers. We analyze the principle of remote control using percolation dynamics by showing analytically and numerically that, with the adaptive generation of a small number of new links in the control layer, not only is this layer but also other layers become dramatically more resistant to cascading failures. We also find that remote control is more effective for scale-free than for random networks. Remote intervention of multilayer network systems through adaptation has real-world applications, which we illustrate using the rail and coach transportation system in the Great Britain.